2015
DOI: 10.1371/journal.pone.0135942
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Susceptibility Genes in Chinese Population: A Field Synopsis and Meta-Analysis of Genetic Association Studies

Abstract: BackgroundEpidemiological studies to date have evaluated the association between genetic variants and the susceptibility to obstructive sleep apnea (OSA). However, the results of these studies have been inconclusive. In this current study we performed meta-analysis of genetic association studies (GAS) to pool OSA-susceptible genes in Chinese population, to perform a more precise evaluation of the association.MethodsVarious databases (i.e., PubMed, EMBASE, HuGE Navigator, Wanfang and CNKI) were searched to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
(54 reference statements)
0
16
0
2
Order By: Relevance
“…Respiratory indices were log-transformed to chronic intermittent hypoxia, the expression of PPAR-gamma was found to be decreased (Zhang, Zhang, Li, & Hou, 2017). In humans, polymorphism Pro12Ala of the PPAR-gamma gene was associated with susceptibility to OSA (Sun et al, 2015) and increased risk of hyperlipidaemia in OSA patients in a Chinese population (Chen et al, 2017). Polymorphism of APOE E2 and E4 alleles are linked to higher LDL-cholesterol and lower HDL-cholesterol levels (Kataoka et al, 1996).…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…Respiratory indices were log-transformed to chronic intermittent hypoxia, the expression of PPAR-gamma was found to be decreased (Zhang, Zhang, Li, & Hou, 2017). In humans, polymorphism Pro12Ala of the PPAR-gamma gene was associated with susceptibility to OSA (Sun et al, 2015) and increased risk of hyperlipidaemia in OSA patients in a Chinese population (Chen et al, 2017). Polymorphism of APOE E2 and E4 alleles are linked to higher LDL-cholesterol and lower HDL-cholesterol levels (Kataoka et al, 1996).…”
Section: F I G U R Ementioning
confidence: 99%
“…Apart from these, common genetic loci can also contribute to the co-occurrence of OSA and cardiometabolic disease. For instance, polymorphisms of the peroxisome proliferator-activated receptor (PPAR) gamma have been associated with obesity, diabetes (Janani & Ranjitha Kumari, 2015), hyperlipidaemia (Chen et al, 2017) and OSA (Sun, Hu, Tu, Zhong, & Xu, 2015). Polymorphisms of the apolipoprotein E (APOE) gene are linked to dyslipidaemia (Kataoka et al, 1996) as well as OSA (Uyrum et al, 2015;Xu, Qian, Guan, Yi, & Yin, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OSA affects more than 10% of adults (2) and increases risk of adverse health outcomes, including hypertension and cardiovascular disease as well as increased mortality (3)(4)(5). Candidate gene studies have identified associations between the apnea hypopnea index (AHI), the chief disease defining metric, measured continuously or dichotomized, with variants in genes associated with inflammation, serotoninergic pathways and ventilatory control (6)(7)(8). We have recently identified the first genome-wide significant associations with objectively measured OSA traits (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Варианты генов C-реактивного белка (CRP) и IL-6 могут быть связаны с наличием СОАГС в детском возрасте [47]. Исследования демонстрируют корреляцию однонуклеотидных полиморфизов в гене TNF-α и формировании СОАГС [48].…”
unclassified